2018
DOI: 10.5430/ijh.v4n1p42
|View full text |Cite
|
Sign up to set email alerts
|

A hypertension control quality improvement pilot program: Experiences and blood pressure outcomes from physician practices

Abstract: Improving Health Outcomes: Blood Pressure (IHO: BP) was a Quality Improvement (QI) pilot program developed by the American Medical Association (AMA) and Johns Hopkins Medicine aimed at helping physicians and their care teams better manage patients with uncontrolled hypertension. The pilot study was conducted at 10 ambulatory practice sites between October 2013 and November 2014 in which the initiative was to devise a framework and intervention strategies for improving hypertension control. The program included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Most studies shown reductions in average SBP with use of AOBP compared to manual BP measurements [5,10,11], and this reduction has been largely attributed to mitigation of white coat effect. Our finding of higher BP with standardized BP measurement protocol vs. manual BP measurement has been reported by one other published study which found lower estimates of BP control in four out of ten clinics after implementation of a quality improvement program for hypertension which included AOBP [12]. Lower rates of BP control in these four clinics were attributed to attenuation of digit preference in that study [12,13].…”
Section: Discussionsupporting
confidence: 81%
“…Most studies shown reductions in average SBP with use of AOBP compared to manual BP measurements [5,10,11], and this reduction has been largely attributed to mitigation of white coat effect. Our finding of higher BP with standardized BP measurement protocol vs. manual BP measurement has been reported by one other published study which found lower estimates of BP control in four out of ten clinics after implementation of a quality improvement program for hypertension which included AOBP [12]. Lower rates of BP control in these four clinics were attributed to attenuation of digit preference in that study [12,13].…”
Section: Discussionsupporting
confidence: 81%
“…Thus, 6 months of practice facilitation combined with ongoing monthly reports (Figure S1) including patient-level data appears sufficient to sustain meaningful improvement in hypertension control. With successful completion of the MAP framework and 2 pilot studies, 12 14 the 3 components of the MAP protocol and logic model (Figure S2) were adapted to support Target: BP, a national hypertension quality improvement initiative of the American Heart Association and American Medical Association. 3…”
Section: Discussionmentioning
confidence: 99%
“…The development and stream-lining of MAP have been described. 12 14 Approximately 20 hours of practice facilitation was provided to each clinical site during the first 6 months of MAP by a single trained individual. Goals of facilitation were to provide education, support, and logistical problem-solving necessary to incorporate MAP into the unique patient flow operations of each clinical site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One common way to use EHR dashboards is as an "information hub", providing a glimpse of the patient's condition as well as offering tools to explore specific aspects of the patient's health and medical history in more detail. Studies have shown improvements in decision-making and patient outcomes with the increased use of EHR dashboards (Bakos, Zimmermann, & Moriconi, 2012;Etamesor, Ottih, Salihu, & Okpani, 2018;Franklin et al, 2017;Khan et al, 2018). Moreover, navigation patterns in EHRs may differ between cued and non-cued events.…”
Section: Introductionmentioning
confidence: 99%